Micro-mechanism analysis of Zhongchuan loess liquefaction disaster induced by Jishishan M6.2 earthquake in 2023 - Wang Yi; Wang Qian; Zhang Wuyu; Zhong Xiumei; Liu Fuqiang; Jia Shichao; Hu Xuefeng (Open Geosciences)
On December 18, 2023, the M S 6.2 Jishishan earthquake triggered a large-scale liquefaction disaster of loess sites in Jintian and Caotan villages, Zhongchuan town, Minhe County, Haidong City, Qinghai Province. To clarify the micro-mechanism of the liquefaction disaster, the Q3 Malan loess layer of the disaster site and its overlying red silty clay layer samples were selected and quantitatively analyzed for the differences in physical properties, structure, microstructural parameters, and mineral compositions. Based on the discrepancy results, the micro-mechanisms between loess microstructure and macro-mechanical properties of soil and liquefaction disaster were investigated. The research shows that compared with red silty clay, the dynamic index of loess corresponding to the physical indices of Zhongchuan loess obviously exceeds the critical threshold of liquefaction under actual seismic intensity. Additionally, its pore structure is dominated by point contact and weakly cemented overhead macropore structure, and its quantitative pore microstructure parameters and mineral composition show significant liquefaction potential. The comprehensive analysis of the liquefaction mechanism shows that the rapid deformation of the soil skeleton and the destruction of the cementation and contact system of the water-sensitive minerals under seismic loading and hydraulic force lead to the collapse of the overhead macropores, the damage of structural strength, the increase of the complex pore channels, the rapid accumulation of pore water pressure, and the reduction of the effective stress, which leads to the liquefaction of the loess.